Effect of vacuum spray drying on the physicochemical properties, water sorption and glass transition phenomenon of orange juice powder. (January 2016) - Islam, M.Z.; Kitamura, Yutaka; Yamano, Yoshitsugu; Kitamura, Mai
Abstract: Vacuum spray drying is a new technique used to produce concentrated orange juice powder using maltodextrin as a drying agent. The dryer was developed for the low-temperature (40–50 °C) drying powderization of liquefied food using superheated steam (200 °C) as a heating medium. The physicochemical properties of orange juice powder with four different combinations of juice solids: maltodextrin solids at 60:40, 50:50, 40:60, and 30:70 were determined. The moisture content, hygroscopicity, water activity, particle size, particle morphology, color characteristics, rehydration and ascorbic acid retention were significantly affected by the maltodextrin concentration and drying conditions. Water sorption and the glass transition temperature of orange juice powder conditioned at various water activities were also evaluated. The obtained data were well fitted to both BET and GAB models. A strong plasticizing effect of water on Tg was able to predicted by the Gordon–Taylor model, where Tg was greatly reduced by the increasing moisture content of the powder. Highlights: The vacuum spray dryer was used to produce orange juice powder at a low temperature drying using superheated steam. VSD orange powders were stable due to their low monolayer moisture content and low water activity. VSD was able to retain a maximum amount of ascorbic acid in orange juice powder.​